2004
DOI: 10.1080/10715760410001694044
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Uric Acid in Rheumatoid Arthritis: Is Allantoin a Marker of Oxidative Stress?

Abstract: Free radicals are implicated in many diseases including atherosclerosis, cancer and also in rheumatoid arthritis. Reaction of uric acid with free radicals, such as hydroxyl radical and hypochlorous acid (HOCl) results in allantoin production. In this study, we measured the serum allantoin levels, oxidation products of uric acid, as a marker of free radical generation in rheumatoid arthritis. Fasting blood samples were obtained from 21 rheumatoid patients and 15 healthy controls. In this study, the serum allant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 36 publications
1
51
0
2
Order By: Relevance
“…Concentration of allantoin was used as a marker for oxidation of uric acid. The levels of allantoin determined by the authors of the study ranged 17.0-27.2 µmol/l in patients and 10.1-17.0 µmol/l in healthy adults [24]. Much lower concentrations of allantoin in plasma were found by Turner et al [25].…”
Section: Allantoinmentioning
confidence: 83%
See 3 more Smart Citations
“…Concentration of allantoin was used as a marker for oxidation of uric acid. The levels of allantoin determined by the authors of the study ranged 17.0-27.2 µmol/l in patients and 10.1-17.0 µmol/l in healthy adults [24]. Much lower concentrations of allantoin in plasma were found by Turner et al [25].…”
Section: Allantoinmentioning
confidence: 83%
“…Allantoin concentrations are estimated at the level of a few/several micromoles per litre. However, older studies showed much higher concentrations of allantoin [16,24] than those performed by the more recent instrumental techniques [21,25]. Current methods, both liquid and gas chromatography with mass spectrometry are more sensitive and more specific.…”
Section: Allantoinmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed significantly higher levels of allantoin in the aged rat urine as compared with young. The elevated allantoin content is again a reflection of increased oxidative stress in the aged rats [40][41][42].…”
Section: Discussionmentioning
confidence: 99%